Colon capsule endoscopy as possible filter test for colonoscopy selection in a screening population with positive fecal immunology - Holleran, Grainne; Leen, Ronan; O’Morain, Colm; McNamara, Deirdre (Endoscopy, 2014)
Background and study aims: Stool tests are highly useful in colorectal cancer (CRC) screening programs; however, they are not as specific as users would like, and place a major burden on resources and subject a number of patients to the risks of invasive optical colonoscopy unnecessarily. Colon capsule endoscopy (CCE) has the potential to reduce the need for optical colonoscopy. To date, the role of CCE in a fecal immunological test (FIT)-based CRC screening program has not been formally evaluated. The aims of this study were to assess the sensitivity, specificity, and negative and positive predictive values of CCE compared with optical colonoscopy in an FIT-positive CRC screening cohort.Patients and methods: A prospective comparison study of CCE compared with optical colonoscopy was undertaken within the second round of a FIT-based bowel screening pilot. Participants with a positive FIT result were invited to undergo both CCE and optical colonoscopy. CCE was performed on Day 1 and optical colonoscopy was performed the following morning. Results: A total of 62 participants were recruited. Optical colonoscopy detected at least one polyp in 36 participants (58 %), significant lesions in 18 (29 %), and cancer in 1 (2 %). There was good correlation between CCE and optical colonoscopy for any lesion and for significant lesions (r = 0.62 and 0.84, respectively). The negative predictive value of CCE was high both for any polyp (90 %) and for significant lesions (96 %).Conclusions: CCE is a safe and effective means of detecting cancer and polyps in a positive FIT screening cohort. The results suggest that CCE would be a useful “filter test” in this situation, and would reduce the number of colonoscopies performed by 71 %.